Methods and Phenomena of Single and Coupled Floor Vibrations — Measurements in Apartment and Office Buildings. Issue 2 (June 2015) - Auersch, Lutz; Said, Samir
A survey of the phenomena and methods for floor vibrations is presented. Experimental results of floor vibrations are shown for many floors in six different buildings. The signals have been evaluated for waves and modes by simple procedures. General rules have been established between the material and the area of a specific floor, and its local eigenfrequency. The damping values of the floor vibrations have been found between D = 1 and 10 % where somewhat higher values have been measured for wooden floors, and a weak correlation with the eigenfrequency has been established. The velocities of bending waves propagating in a storey and the attenuation with distance in the building have been analysed. A considerable transfer of vibration from one room to far away parts of the building has been found in the studied buildings with concrete and wooden floors. An example building has been analysed for modes of coupled floor bays. The strong coupling of similar neighbouring floor bays would yield a wide band of global resonance frequencies. The measured wooden floor exhibits a weak coupling of the neighbouring floor bays and a narrower band of eigenfrequencies. A special method has been tested with the impulse measurements to estimate the coupled eigenmodes in presence of the high damping. From the ambient measurement, a low-frequency vibration mode has been detected which includes the vibration of the whole building and the soil. The coupling of floors to other floors and the whole building is an important phenomenon of structural dynamics which should be observed for the prediction of vibration due to internal and external sources.